Understanding and characterizing the services sector in South Africa: An update - Francois Steenkamp; Yanele Nyamela; Megan Bryer; Siyanda Jonas (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2025)
This paper examines the services sector's contribution to the South African economy and the extent to which the sector can drive structural transformation. The South African economy has continued along a path of tertiarization and can be classified as a de facto services-based economy. Relatively highproductivity modern services activities, including financial, business, and communication services, have become increasingly important. The paper applies subnational economic complexity analysis and shows that at the district level, higher levels of economic complexity are associated with higher levels of economic development. The most complex industries fall within the modern services sector, and the industry space analysis shows that these complex industries are clustered and highly connected. The most complex district economies are those orientated towards these modern services activities. Complex manufacturing activities are also present within these complex district economies, pointing to a degree of interdependence between activities across these two key sectors.
Keywords: O14; O25; O38; R12; 330; economic complexity; relatedness; structural transformation; servicification; economic development